'Best. Show. Eever.': Who killed Veronica Mars?. Issue 1 (1st April 2013) - Paproth, Matthew
In this article, I argue that Veronica Mars is a fruitful site for critical analysis as a result of its position between cult and mainstream fandom. As a result of network pressure, writer-creator Rob Thomas made significant changes to both the show's structure and content; simultaneously, he positioned it as a cult-television haven for fans of Buffy the Vampire Slayer, which had recently gone off the air. This deliber-ate positioning, coupled with Thomas's openness about the process and the surprising willingness of cult fans to cooperate, makes it a unique case study in the business of popular television.